2016
DOI: 10.1530/eje-16-0447
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor gene CAG repeat 
in relation to 4-year changes in 
androgen-sensitive endpoints in 
community-dwelling older European men

Abstract: 63were independent of baseline T or oestradiol (E2) levels. 64Results: The AR CAG repeat, when used as a continuous or categorical predictor, was not 65 associated with longitudinal changes in ASEs or medical conditions after adjustments. These results 66were independent of T and E2 levels. 67Conclusion: Within a 4-year timeframe, variations in the AR CAG repeat do not contribute to the rate 68 of phenotypic ageing, over and above, that, which might be associated with the age-related decline in 69 T levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This implies that testosterone may act via both genomic and nongenomic mechanisms exerting opposite effects on HDL‐C levels . Furthermore, recent evidence suggest against significant associations between the AR CAG repeat and longitudinal changes in metabolic parameters, leaving the role of CAG repeat still tentative . In spite of genetic screening of AR CAG polymorphism remains as a potential valuable screening tool in predicting those at higher risk of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that testosterone may act via both genomic and nongenomic mechanisms exerting opposite effects on HDL‐C levels . Furthermore, recent evidence suggest against significant associations between the AR CAG repeat and longitudinal changes in metabolic parameters, leaving the role of CAG repeat still tentative . In spite of genetic screening of AR CAG polymorphism remains as a potential valuable screening tool in predicting those at higher risk of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…We also focus on T and the modulatory effect of AR‐CAGn on androgen‐associated somatic traits, but other proteins and hormones such as sex‐hormone binding globulin and estrogen (E2) play important role in these traits (Ponce‐González et al, ). Indeed, aromatization of T to E2 in adipose tissue may explain inconsistencies in the relationship between AR‐CAGn and T on androgen‐associated traits across studies (De Naeyer et al, ; Eendebak et al, ). However, elevated E2 levels arising from aromatization of T in adipose tissue should be relatively low among the men in our study, who are quite lean as compared to men in most Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous small cross‐sectional studies have reported variable changes to metabolic risk factors in relation to CAG repeat length . More recently, however, two large European longitudinal studies of community‐dwelling men reported no correlation between CAG repeat length and metabolic indicators . One explanation for the absence of clear genotype‐phenotype association is that testosterone has actions that are mediated through pathways not involving androgen receptors, for instance, via conversion to non‐androgenic metabolites such as estradiol .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] More recently, however, two large European longitudinal studies of community-dwelling men reported no correlation between CAG repeat length and metabolic indicators. 25,26 One explanation for the absence of clear genotypephenotype association is that testosterone has actions that are mediated through pathways not involving androgen receptors, for instance, via conversion to non-androgenic metabolites such as estradiol. 27 It is also possible that the effects of CAG repeat length are altered by testosterone availability.…”
Section: Discussionmentioning
confidence: 99%